The impact of digital elevation models resolution on tectonic activity assessment based on morphotectonic indices: a case study of Seulawah Agam Volcano, Indonesia - Muhammad Ronggour Pardamean Siahaan; Emi Sukiyah; Nana Sulaksana; Agus Didit Haryanto (Journal of Degraded and Mining Lands Management, 2023)
The Digital Elevation Number (DEM) is the main tool for quantitative geomorphological tests. Furthermore, Shuttle Radar Topography Mission (SRTM) images with a resolution of 30 m have been widely used as a source of DEM data in geomorphological studies, while DEMNAS (National DEM) images with 8 m are rarely used. Both images can identify typical volcanic morphology based on a visual comparison of hillshade with certain variations in slope. The objective of this study was to determine the feasibility of DEM for tectonic activity assessment based on morphotectonic indices. In this study, geomorphological comparisons were carried out on twelve watersheds in the Seulawah Agam Volcano (SAV). The data extraction of DEM resulted in the total area and perimeter, namely 486.8 km2 and 455 km (SRTM), as well as 482.8 km2 and 460.3 km (DEMNAS). The total segments up to the 4th order and the resulting lengths were 290 and 512.8 km for SRTM, while DEMNAS were 527 and 711.7 km. The morphotectonic variables used included drainage density, bifurcation, circularity, and valley floor ratio, as well as basin shape index. The results of these parameter calculations using mean values of SRTM imagery showed very coarse textures, deformed, more elongated, moderate tectonic, and low uplift. On the other hand, those of DEMNAS imagery showed coarse textures, not-deformed, more elongated, low tectonic, and low uplift of the basin’s characteristics.